Transformation of the CIRC Learning Model Assisted by Google Sites: A Study of Development and Practicality - Darmansyah, Murti; Jufri; Juanda; Mantasiah (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to develop a Cooperative Integrated Reading and Composition (CIRC) learning model supported by Google Sites, proven to be practical in enhancing literacy skills among junior high school students. The research employed a Research and Development (R&D) methodology using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The research subjects included teachers and students representing three literacy proficiency levels (low, medium, and high) in Majene Regency. The practicality of the model was assessed through implementation observations and response questionnaires administered to both teachers and students. Limited testing revealed an implementation rate of 89% (categorized as highly practical), with response scores of 77.40 (students) and 79.80 (teachers). In the extended trial, the implementation rate reached 96.82%, with response scores of 77.54 (students) and 85.43 (teachers). These findings indicate that the Google Sites-assisted CIRC model is highly practical for classroom use and significantly contributes to the development of technology-based pedagogical practices, particularly in improving students’ reading and writing literacy. This study reinforces the role of technology in promoting interactive, collaborative, and contextual learning in Indonesian language and literature education.